Fracture-based Fabrication of Normally-closed, Adjustable and Fully Reversible Micro-scale Fluidic Channels - Kim, Byoung Choul (2014)
Adjustable fluidic structures play an important role in microfluidic systems. Fracture of multilayered materials under applied tension has been previously demonstrated as a convenient, simple and inexpensive approach to fabricate nano-scale adjustable structures; here, we demonstrate how to extend this concept to the micro-scale. We achieve this by a novel pairing of materials that leverages fracture mechanics to limit crack formation to a specified region, allowing us to create size-controllable and adjustable microfluidic structures. We demonstrate that this technique can be used to fabricate ‘normally-closed’ microfluidic channels that are completely reversible, a feature that is challenging to achieve in conventional systems without careful engineering controls. The adjustable microfluidic channels are then applied to mechanically lyse single cells, and subsequently manipulate the released nuclear chromatin, creating new possibilities for epigenetic analysis of single cells. This simple, versatile and robust technology provides an easily accessible pathway to construct adjustable microfluidic structures, which will be useful in developing complex assays and experiments even in resource-limited settings.